2009
DOI: 10.1002/cne.22028
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic substantia nigra grafts in the mesencephalon send neurites to the host striatum in non‐human primate after overexpression of GDNF

Abstract: In spite of partial success in treating Parkinson's disease using ectopically placed grafts of dopamineproducing cells, restoration of the original neuroanatomical circuits, if possible, might work better. Previous evidence of normal anatomic projections from ventral mesencephalic (VM) grafts placed in the substantia nigra (SN) has been limited to neonatal rodents and double grafting or bridging procedures. This study attempted to determine whether injection of a potent growth promoting factor, glial cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Interestingly, the target‐directed outgrowth and functional benefit reported by Thompson and colleagues was further enhanced by overexpression of recombinant adeno‐associated virus (rAAV)‐ GDNF gene therapy delivered to the striatum 228. In support, recent work from Redmond and colleagues demonstrated that rAAV2‐mediated gene transfer of GDNF to the striatum of MPTP‐treated monkeys resulted in a marked increase in survival of primary fetal VM DA‐precursor cells by several‐fold and elicited directional outgrowth of axons 232,233. The combined results support the proof‐of‐concept of cell transplantation combined with gene therapy for nigrostriatal reconstruction in PD.…”
Section: Neuronal Transplantation In Parkinson's Diseasementioning
confidence: 64%
“…Interestingly, the target‐directed outgrowth and functional benefit reported by Thompson and colleagues was further enhanced by overexpression of recombinant adeno‐associated virus (rAAV)‐ GDNF gene therapy delivered to the striatum 228. In support, recent work from Redmond and colleagues demonstrated that rAAV2‐mediated gene transfer of GDNF to the striatum of MPTP‐treated monkeys resulted in a marked increase in survival of primary fetal VM DA‐precursor cells by several‐fold and elicited directional outgrowth of axons 232,233. The combined results support the proof‐of‐concept of cell transplantation combined with gene therapy for nigrostriatal reconstruction in PD.…”
Section: Neuronal Transplantation In Parkinson's Diseasementioning
confidence: 64%
“…Functional recovery could be mediated by neurotrophic support, new synaptic circuit elaboration, and enhancement of the stroke-induced neuroplasticity (74). Recent findings of transplanted embryonic dopamine (DA) neurons into the substantia nigra (SN) indicate that DA neurons could extend neurites towards a desired target through the brain stem and caudal diencephalon to reconstruct the neural circuitry from grafted neurons in the host (315,355). Application of stem cells for neuroreplacement therapy is therefore no longer science fiction—it is science fact (367).…”
Section: Neurorestorative Mechanisms Of Cell Therapymentioning
confidence: 99%
“…GDNF has been used successfully to increase the survival of fetal dopaminergic cell transplants in the 6-OHDA-lesioned rat striatum (Rosenblad et al, 1996; Yurek, 1998). Viral mediated over-expression of GDNF within the striatum establishes a gradient that induces axon growth into the striatum from dopaminergic neurons within nigral transplants in both mouse and non-human primate models (Thompson et al, 2009; Kordower et al, 2000; Redmond et al, 2009). These studies were performed in partially lesioned animals, and in the mouse model complete lesions showed no growth of transplanted axons toward the striatum, indicating surviving endogenous dopaminergic axons might act as a growth supportive scaffold.…”
Section: Introductionmentioning
confidence: 99%